DLX4 is associated with orofacial clefting and abnormal jaw development - Wu, Di; Mandal, Shyamali; Choi, Alex; Anderson, August; Prochazkova, Michaela; Perry, Hazel; Gil-Da-Silva-Lopes, Vera L; Lao, Richard; Wan, Eunice; Tang, Paul Ling-Fung; Kwok, Pui-yan; Klein, Ophir; et al. (Human molecular genetics, 2015)
Cleft lip and/or palate (CL/P) are common structural birth defects in humans. We used exome sequencing to study a patient with bilateral CL/P and identified a single nucleotide deletion in the patient and her similarly affected son—c.546_546delG, predicting p.Gln183Argfs*57 in the Distal-less 4 (DLX4) gene. The sequence variant was absent from databases, predicted to be deleterious and was verified by Sanger sequencing. In mammals, there are three Dlx homeobox clusters with closely located gene pairs (Dlx1/Dlx2, Dlx3/Dlx4, Dlx5/Dlx6). In situ hybridization showed that Dlx4 was expressed in the mesenchyme of the murine palatal shelves at E12.5, prior to palate closure. Wild-type human DLX4, but not mutant DLX4_c.546delG, could activate two murine Dlx conserved regulatory elements, implying that the mutation caused haploinsufficiency. We showed that reduced DLX4 expression after short interfering RNA treatment in a human cell line resulted in significant up-regulation of DLX3, DLX5 and DLX6, with reduced expression of DLX2 and significant up-regulation of BMP4, although the increased BMP4 expression was demonstrated only in HeLa cells. We used antisense morpholino oligonucleotides to target the orthologous Danio rerio gene, dlx4b, and found reduced cranial size and abnormal cartilaginous elements. We sequenced DLX4 in 155 patients with non-syndromic CL/P and CP, but observed no sequence variants. From the published literature, Dlx1/Dlx2 double homozygous null mice and Dlx5 homozygous null mice both have clefts of the secondary palate. This first finding of a DLX4 mutation in a family with CL/P establishes DLX4 as a potential cause of human clefts.
Keywords: Cleft Palate; dánio pruhované; Animals; HeLa Cells; Cleft Lip; transkripční faktory; Morpholinos; Gene Expression Regulation, Developmental; Jaw Abnormalities; Mice, Knockout; Exome; myši knockoutované; High-Throughput Nucleotide Sequencing; lidé; HeLa buňky; rozštěp patra; Mice; exom; Transcription Factors; homeodoménové proteiny; abnormality čelisti; mozek; Zebrafish Proteins; proteiny dánia pruhovaného; myši; rozštěp rtu; Zebrafish; morfolino; Brain; Mesoderm; mezoderm; vysoce účinné nukleotidové sekvenování; kostní morfogenetický protein 4; Homeodomain Proteins; zvířata; vývojová regulace genové exprese; Bone Morphogenetic Protein 4; Humans